Ectopic Expression of Kenaf (Hibiscus cannabinus L.) HcWRKY50 Improves Plants’ Tolerance to Drought Stress and Regulates ABA Signaling in Arabidopsis - Xiaoping Niu; Meixia Chen; Zeyuan She; Mohammad Aslam; Jianmin Qi; Yuan Qin (Agronomy, 2022)
Kenaf (Hibiscus cannabinus L.) is an environmentally friendly, multipurpose fiber crop suitable for osmotic stress tolerance studies. However, the mechanisms of tolerance remain largely unknown. Here, we identified a stress-responsive HcWRKY50 gene from kenaf (Hibiscus cannabinus L.) and studied its function and tolerance under drought stress. HcWRKY50 is a nuclear-localized protein. The overexpression of HcWRKY50 in Arabidopsis showed higher drought tolerance, exhibiting increased root length and lateral root number, and reduced stomatal density compared with the control lines. The seed germination and seedling growth of HcWRKY50 transgenic plants showed less sensitivity to ABA but they became more sensitive to ABA in their stomatal aperture. Furthermore, qRT-PCR analysis revealed that HcWRKY50 regulated ABA signaling by promoting the expression of several key ABA-responsive and stress-responsive genes such as RD29B and COR47 in transgenic lines. Taken together, this study demonstrated that the kenaf transcription factor HcWRKY50 regulates seed germination and seedling growth and improves drought stress tolerance via an ABA signaling pathway.